Review of Network Economics (De Gruyter, 2002)
Since 2002, the Review of Network Economics (RNE) has been a leading forum for new insights in network economics, providing essential reading for anyone interested in the economics of network industries. It seeks to help policy makers, academics, and practitioners keep informed of new research and policy debate in network economics and related subjects that are relevant to the study of network industries.